Manual procedure for Muslim Friendly Hospitality Services (MFHS) certification 2017 - Zawawi, Majdah; Ramli, Noriah; Abas, Afridah; Muhamad, Zulkefli; Shahidin, Faridah; Azmi, Ida Madieha; Bahli, Saifol; Rahim, Muhamad Jabal; Harun, Muhamad Ilyas (Department of Standard Malaysia, 2017)
Manual Procedure for Muslim Friendly Hospitality Services (MFHS) Certification is a reference document for the MFHS certification which is concurrently used together with the MS2610:2015. It explains the terms and requirements for certification, information about application procedures, certification processes, fee charges and others. Doc. code: MS2610:2015 – 001/2017